2019
DOI: 10.1155/2019/4325105
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair Deficiency in Breast Cancer: Opportunities for Immunotherapy

Abstract: Historically the development of anticancer treatments has been focused on their effect on tumor cells alone. However, newer treatments have shifted attention to targets on immune cells, resulting in dramatic responses. The effect of DNA repair deficiency on the microenvironment remains an area of key interest. Moreover, established therapies such as DNA damaging treatments such as chemotherapy and PARP inhibitors further modify the tumor microenvironment. Here we describe DNA repair pathways in breast cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 166 publications
(148 reference statements)
0
15
0
Order By: Relevance
“…Assessing the presence of pathogenic somatic variants in CHEK2 and PALB2 genes is not common practice. In breast cancer patients, somatic changes may be present in other genes involved in DNA repair: (1) homologous recombination ( ATM , ATR , CHEK1 , CHEK2 , BARD1 , RAD51 , NBS1 , PALB2 , FANCD2 ), (2) non-homologous end joining ( DNA-PK , KU70/80 ), (3) mismatch repair ( MLH1 , MSH1 , MSH6 , PMS2 ), (4) base excision repair ( APE1 , XRCC1 , ERCC2 ) [ 40 ]. It is worth highlighting that there are different commercial panel tests to examine a wide range of genes related to breast cancer employing the NGS technique.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the presence of pathogenic somatic variants in CHEK2 and PALB2 genes is not common practice. In breast cancer patients, somatic changes may be present in other genes involved in DNA repair: (1) homologous recombination ( ATM , ATR , CHEK1 , CHEK2 , BARD1 , RAD51 , NBS1 , PALB2 , FANCD2 ), (2) non-homologous end joining ( DNA-PK , KU70/80 ), (3) mismatch repair ( MLH1 , MSH1 , MSH6 , PMS2 ), (4) base excision repair ( APE1 , XRCC1 , ERCC2 ) [ 40 ]. It is worth highlighting that there are different commercial panel tests to examine a wide range of genes related to breast cancer employing the NGS technique.…”
Section: Discussionmentioning
confidence: 99%
“…PARPi have shown effectiveness in tumors with deficiencies in our DEGs such as RAD51, FANCD2, FANCA, CHK1 and XRCC2 [ 118 120 ]. For BRCA1/2 mutant breast cancers, PARPi olaparib and talazoparib are now FDA-approved monotherapies [ 119 , 121 , 122 ]. Other studies also showed that their effectiveness extend to tumors without BRCA-mutations [ 117 , 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, PARP inhibitors (PARPi) serve as an example of the targeted therapy [117]. PARPi have shown effectiveness in tumors with deficiencies in our DEGs such as RAD51, FANCD2, FANCA, CHK1 and XRCC2 [118][119][120]. For BRCA1/2 mutant breast cancers, PARPi olaparib and talazoparib are now FDA-approved monotherapies [119,121,122].…”
Section: Implications Of Overexpression Of Dna Repair Genes On Precismentioning
confidence: 99%
“…The multiple cancer mutations taking place in humans are continuously corrected by the immune cells. However, if the number or function of the immune cells decreases, there may be an increased risk of cancer development (Dunn, Bruce, Ikeda, Old, & Schreiber, 2002;Gilmore, Mccabe, Kennedy, & Parkes, 2019).…”
Section: Risk Of Bias Highmentioning
confidence: 99%